Pentingnya Perlindungan Konsumen dalam Transaksi Jual Beli - Elpha, Meriza; Sofiani , Dwi; Hanif, Ihwatul; Vivian, Lili; Febdillah, Riza (Jurnal Hukum dan Demokrasi (JHD), 2024)
Buying and selling is a common activity in Indonesian society, and every day there are people involved in buying and selling transactions. Buying and selling refers to a transaction between a seller, who is usually a business actor, and a buyer, who is a consumer. In the buying and selling process, consumers often face problems or losses. Therefore, Indonesia has issued a consumer protection law to protect consumer rights. The problems faced by consumers are not limited to selecting goods alone, but involve more complex problems related to the awareness of all parties, including business actors and consumers, about the importance of consumer protection. The aim of implementing, developing and regulating consumer protection is to increase consumer dignity and awareness. More than that, it also aims to encourage business actors not to abuse their business practices and act responsibly. It is important for consumers to realize that they have rights protected by the Consumer Protection Law, so that they can exercise social control over the behavior and business practices of business actors and the government. This research uses socio-legal research methods that adopt an interdisciplinary approach or a "hybrid" approach that combines aspects of sociological research with a normative approach that applies qualitative analysis. The results of this article state that consumer protection law has great significance in the context of buying and selling activities. For business actors, this law is important because it provides clear guidelines regarding permitted practices and prohibits actions that could harm consumers. Meanwhile, for consumers, consumer protection laws are also important because they provide security guarantees when they are involved in buying and selling transactions